2020
DOI: 10.1186/s12985-020-01327-9
|View full text |Cite
|
Sign up to set email alerts
|

First report of Lihan Tick virus (Phlebovirus, Phenuiviridae) in ticks, Colombia

Abstract: Background: Tick-borne phenuivirus (TBPVs) comprise human and animal viruses that can cause a variety of clinical syndromes ranging from self-limiting febrile illness to fatal haemorrhagic fevers. Objective: Detect Phlebovirus (Family Phenuiviridae) in ticks collected from domestic animals in Córdoba, Colombia. Methods: We collected 2365 ticks from domestic animals in three municipalities of the Department of Cordoba, Colombia in 2016. Ticks were identified and pooled by species for RNA extraction. A nested re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
(31 reference statements)
0
5
0
1
Order By: Relevance
“…In 2015, LTPV was first found in R. microplus ticks from China and has since been found in other countries (Li et al 2015 ; López et al 2020 ). This virus is a Phlebovirus -like.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, LTPV was first found in R. microplus ticks from China and has since been found in other countries (Li et al 2015 ; López et al 2020 ). This virus is a Phlebovirus -like.…”
Section: Discussionmentioning
confidence: 99%
“…LTV was first described in Chinese R. microplus ( Li et al, 2015 ) and reported in Turkish H. marginatum and R. sanguineus ticks ( Dincer et al, 2017 ; Brinkmann et al, 2018 ), and Colombian Dermacentor nitens ticks ( Lopez et al, 2020 ). LTV GD was closely related to the variants found in China ( Xu et al, 2021 ), France ( Gondard et al, 2020 ), and Brazil ( Souza et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, there has been a dramatic increase in the number of discovered viruses that are transmitted by arthropods [ 1 , 2 , 3 , 4 ]. Some of them are pathogenic for humans and mammals [ 2 , 5 , 6 ], and the pathogenic potential of others is unknown [ 1 , 3 , 4 ]. Many recently discovered arthropod viruses belong to the genus Orthoflavivirus [ 1 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, there has been a dramatic increase in the number of discovered viruses that are transmitted by arthropods [1][2][3][4]. Some of them are pathogenic for humans and mammals [2,5,6], and the pathogenic potential of others is unknown [1,3,4].…”
Section: Introductionmentioning
confidence: 99%